2020
DOI: 10.13004/kjnt.2020.16.e18
|View full text |Cite
|
Sign up to set email alerts
|

Can Supine Magnetic Resonance Imaging Be an Alternative to Standing Lateral Radiographs for Evaluating Cervical Sagittal Alignment?

Abstract: Objective Recently, many studies have reported that cervical alignment is related to clinical outcomes. However, poor visibility of anatomical structures during X-ray (XR) imaging limits accurate measurements. In supine magnetic resonance (MR) imaging, the boundary of the anatomical structure is clear, but the correlation to XR images taken in a standing position is problematic. In this study, we evaluated the agreement of sagittal alignment parameters between MR and XR measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Furthermore, a significant number of patients (50%) were excluded from our analysis because of poor visibility of the T1 superior endplate on lateral XR images; this is in line with similar studies and highlights a notable limitation of this imaging modality to fully assess cervical alignment. 11,12,14 Lastly, we attribute the differences of the cervical SVA and T1 tilt to the differences in imaging position-upright versus supine -however, there are several variables that are unaccounted for and may have influenced our findings. These include inconsistent head positioning, rotation, and differential observer experience with the imaging software.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, a significant number of patients (50%) were excluded from our analysis because of poor visibility of the T1 superior endplate on lateral XR images; this is in line with similar studies and highlights a notable limitation of this imaging modality to fully assess cervical alignment. 11,12,14 Lastly, we attribute the differences of the cervical SVA and T1 tilt to the differences in imaging position-upright versus supine -however, there are several variables that are unaccounted for and may have influenced our findings. These include inconsistent head positioning, rotation, and differential observer experience with the imaging software.…”
Section: Discussionmentioning
confidence: 89%
“…[6][7][8] Efforts to address these shortcomings have been explored using the C7 vertebral body as a proxy for T1-based measurements, [8][9][10] as well as employing advanced imaging such as computed tomography and MRI to better visualize and quantify the parameters of interest. 2,[11][12][13][14] In this domain, findings and conclusions vary; some groups advocate for the utility of MRI as a surrogate for plain x-rays (XR), 11,13 while other groups determined that MRI measurements could not replace XR measurements. 2,12,14 In this context, we analyzed preoperative XR and MRI cervical sagittal parameters for patients undergoing posterior decompressive procedures for cervical spondylotic myelopathy.…”
mentioning
confidence: 99%
“…[15][16][17] However, a supine MRI has not always been suggested as an acceptable alternative to standing radiography. Bae et al 18 evaluated the agreement of the sagittal alignment parameters between MRI and standing radiographs in 268 patients. Although the correlation between MRI and radiography was high, the ICC demonstrated low reliability.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that supine MRI could not replace standing radiographic measurements. 18 It is acknowledged that the Cobb angle is different between the supine and standing positions because of the change of gravitational load on the spine. 19 This gravitational change is associated with almost 5 degrees of loss of the thoracic curve, 29 degrees of loss of the lumbar lordosis, and 20 degrees of loss of the sacral rotation after moving from a standing to a sitting position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation